LC-ESI-Q-TOF-MS identification of porcine-specific peptide biomarker in cooked pork for halal authentication - Zainal Abidin, Siti Aimi Sarah; Wan Jamaluddin, Wan Noor Faradalila; Karsani, Saiful Anuar; Ismail, Amin; Sazili, Awis Qurni (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Identifying pork adulteration in the mixture of meat is nearly impossible with the naked eye. Therefore, with the aid of modern technology, an authentication technique can be developed from various sample state which range from small to molecular level. The present research focused on protein-based method as an approach to differentiate pork from beef, chevon and chicken. Instead of using DNA markers, species authentication using proteomics approach was chosen as the state-of-the-art technology offers high discriminating power and specificity. The purpose of this study was to determine porcine-specific peptide biomarker from thermally processed meat using liquid chromatography electrospray ionization quadrupole time of flight mass spectrometry (LC-ESI-Q-TOF-MS) in which the marker peptides were derived from the trypsin hydrolysis of myosin-4. A thorough investigation of LC-ESI-Q-TOF-MS data revealed two myosin-4 peptides at position 1450-1472 which demonstrated species-specific properties to porcine.